Counter‐regulatory paracrine actions of FGF‐23 and 1, 25(OH)2D in macrophages. Issue 1 (9th January 2016) - Han, Xiaobin; Li, Linqiang; Yang, Jiancheng; King, Gwendalyn; Xiao, Zhousheng; Quarles, Leigh Darryl
Abstract : Mechanisms underlying the association between fibroblastic growth factor 23 (FGF‐23) and inflammation are uncertain. We found that FGF‐23 was markedly up‐regulated in LPS/INF‐γ‐induced proinflammatory M1 macrophages and Hyp mouse‐derived peritoneal macrophages, but not in IL‐4‐induced M2 anti‐inflammatory macrophages. NF‐КB and JAK/STAT1 pathways mediated the increased transcription of FGF‐23 in response to M1 polarization. FGF‐23 stimulated TNF‐α, but not IL‐6, expression in M0 macrophages and suppressed Arginase‐1 expression in M2 macrophages through FGFR‐mediated mechanisms. 1, 25(OH)2 D stimulated Arginase‐1 expression and inhibited FGF‐23 stimulation of TNF‐α. FGF‐23 has proinflammatory paracrine functions and counter‐regulatory actions to 1, 25(OH)2 D on innate immune responses. Abstract :